Functional integration of “undead” neurons in the olfactory system - Prieto-Godino, Lucia L. (Sci Adv, 2020)
Programmed cell death (PCD) is widespread during neurodevelopment, eliminating the surpluses of neuronal production. Using the Drosophila olfactory system, we examined the potential of cells fated to die to contribute to circuit evolution. Inhibition of PCD is sufficient to generate new cells that express neural markers and exhibit odor-evoked activity. These “undead” neurons express a subset of olfactory receptors that is enriched for relatively recent receptor duplicates and includes some normally found in different chemosensory organs and life stages. Moreover, undead neuron axons integrate into the olfactory circuitry in the brain, forming novel receptor/glomerular couplings. Comparison of homologous olfactory lineages across drosophilids reveals natural examples of fate change from death to a functional neuron. Last, we provide evidence that PCD contributes to evolutionary differences in carbon dioxide–sensing circuit formation in Drosophila and mosquitoes. These results reveal the remarkable potential of alterations in PCD patterning to evolve new neural pathways.